PENGARUH AFFIRMATIVE ACTION TERHADAP ELEKTABILITAS CALON PEREMPUAN DALAM PEMILU 2019 DI KOTA DENPASAR - I Ketut Arka (Sekolah Tinggi Pariwisata Mataram, 2021)
This Study aims to determine the effect of affirmative action on the electability of female candidate which has been regulated by our constitution by providing a 30% quote in the list of permanent Candidate for the 2019 general election in Denpasar. This study also aims to provide an overview of the representation of women as election organizers. The methodology used in this study is a qualitative descriptive method. The data collection technique used is observation and documentation sourced from The Denpasar General Election Commission secondary data. After the data is collected data analysis is carried out which include data reduction, data presentation and data verification. From the result of study was found that all political parties participating in the General Election in Denpasar have included at least 30% of their female candidates in each electoral district, but only 2 candidates out of 45 available quotas in parliament. Thus, the author concludes that the affirmative action in the 2019 election does not have a significant effect on the substantially electability of female candidates.